Nucleation of pores and their influence on material properties - Андрій Олександрович Чейлитко (Tehnologìčnij Audit ta Rezervi Virobnictva, 2015)
The pore formation is investigated and the theories of porosity are analyzed. It is proposed classification of the pore genesis, namely the separation on the diffusion genesis of and the destruction genesis. By diffusion genesis it is covered the pore formation at formation of gases in the material due to chemical reactions, to the difference of gas saturation limits of matter in different states of aggregation, to the transition to the gaseous state of one of the components of the original mixture. By destruction genesis – the pore formation by thermal degradation due to deformation of the body, and also due to the effects of radiation, followed by the collapse of the chemical bonds. The author gives a detailed account of each type of pore genesis.